2022
DOI: 10.3390/microbiolres13040056
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Host Small RNA Response to SARS-CoV-2 Infection

Abstract: After two years into the pandemic of the coronavirus disease 2019 (COVID-19), it remains unclear how the host RNA interference (RNAi) pathway and host miRNAs regulate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and impact the development of COVID-19. In this study, we profiled small RNAs in SARS-CoV-2-infected human ACE2-expressing HEK293T cells and observed dysregulated host small RNA groups, including specific host miRNAs that are altered in response to SARS-CoV-2 infection. By com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Interestingly, it has been suggested that many RNA viruses contain "hotspots" that serve as sites for vsRNA production [62], whereby sequences surrounding hotspots might be expected to adopt stable hairpin-like structures predicted by RNAz within the conserved RNA structures [75,76]. This pattern was recently observed by comparing virally derived small RNAs in different SARS-CoV-2-infected samples that are prone to generate vsRNAs [77]. In our case, the vast majority of our Beta-CoV vsRNAs encoded in ORF1a at genome positions ranging from 4153 to 5544 seem to show possible "hotspots", indicating that the nsp3 of ORF1a is deeply involved in vsRNA production [78,79].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, it has been suggested that many RNA viruses contain "hotspots" that serve as sites for vsRNA production [62], whereby sequences surrounding hotspots might be expected to adopt stable hairpin-like structures predicted by RNAz within the conserved RNA structures [75,76]. This pattern was recently observed by comparing virally derived small RNAs in different SARS-CoV-2-infected samples that are prone to generate vsRNAs [77]. In our case, the vast majority of our Beta-CoV vsRNAs encoded in ORF1a at genome positions ranging from 4153 to 5544 seem to show possible "hotspots", indicating that the nsp3 of ORF1a is deeply involved in vsRNA production [78,79].…”
Section: Discussionmentioning
confidence: 91%
“…There are now numerous studies regarding the effects of COVID-19 infection upon miRNA production, both by cells in response to the infection, and by SARS-CoV-2 to promote its own successful infection [99][100][101][102][103][104][105][106][107][108][109][110]. These studies include the effects on gene expression, altered biochemical pathways, interferon signaling, interaction with host mRNAs, and have demonstrated that various miRNAs appear associated with clinical severity including inflammatory and cytokine storm mechanisms [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110]. One study has identified both chemokine (CC) CCL20, inflammatory cytokines IL6 and IL10, and miR-451a as key correlates of fatal COVID-19 [110], i.e., miRNAs are part of a wider whole system response.…”
Section: Covid-19 Infection Alters the Mirna Landscape And Ensuing Ge...mentioning
confidence: 99%
“…Increasing evidence suggests the existence of a close relationship between the SARS-CoV-2 infection and the altered accumulation of endogenous small non-coding RNAs (sncRNAs, or simply sRNAs) 6 , 8 11 . Of note, sncRNAs are pervasive in all kingdoms of life (from prokaryotes to eukaryotes) and they are involved in the regulation of gene expression 12 .…”
Section: Introductionmentioning
confidence: 99%